The objective limits of validity of court decisions on negative claims for recognition - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the problem of the objective limits of the validity of the legal force for judgments on claims for challenging legal relations and claims of invalidity of transactions (other legal acts). The author comes to the conclusion that after the refusal of such a claim, the repeated judicial challenge of the same legal relationship (the validity of the same transaction, other legal act) on other grounds is unacceptable. Similar approaches should be applied to the decisions of the courts on the refusal of the claims for award and the claims for conversion, and, moreover, in non-action proceedings. On this basis, the author makes recommendations on how to improve the practice of applying current procedural legislation.
Keywords: objective limits of the validity of the legal force of the judicial decision; rule of exclusivity; negative claims for recognition; claims for invalidity of transactions; non-action proceedings